Modified poly(caprolactone trifumarate) with embedded gelatin microparticles as a functional scaffold for bone tissue engineering - Al-Namnam, N.M.N.; Kim, K.H.; Chai, W.L.; Ha, K.O.; Siar, Chong Huat; Ngeow, Wei Cheong (Wiley, 2016)
Bone tissue engineering offers high hopes in reconstructing bone defects that result from trauma, infection, tumors, and other conditions. However, there remains a need for novel scaffold materials that can effectively stimulate ossification with appropriate functional properties. Therefore, a novel injectable, biodegradable, and biocompatible scaffold made by incorporating modified poly(caprolactone trifumarate) (PCLTF) with embedded gelatin microparticles (GMPs) as porogen is developed. Specifically, in vitro and in vivo tests were carried out. For the latter, to determine the osteogenic ability of PCLTF-GMPs scaffolds, and to characterize bone-formation, these scaffolds were implanted into critical-sized defects of New Zealand white rabbit craniums. Field Emission Scanning Electron Microscope (FESEM) demonstrated cells of varying shapes attached to the scaffold surface in vitro. The PCLTF-GMPs demonstrated improved biocompatibility in vivo. Polyfluorochrome tracers detected bone growth occurring in the PCLTF-GMPs filled defects. By incorporating PCLTF with GMPs, we have fabricated a promising self-crosslinkable biocompatible and osteoconducive scaffold for bone tissue engineering.